Age and other risk factors related to reentry to care from kin guardian homes. (May 2018) - Parolini, Arno; Shlonsky, Aron; Magruder, Joseph; Eastman, Andrea Lane; Wulczyn, Fred; Webster, Daniel
Abstract: Although kinship guardianship is an increasingly important foster care exit pathway for children in the United States, research on the factors leading to kinship guardianship breakdown is lacking. This study examines the factors associated with guardianship breakdown for children who exited foster care to kinship guardianship in California between 2003 and 2010 (N = 18, 831). Specifying time-dependent Cox relative risk models, children's age trajectories are directly accounted for in the analysis. This allows differentiation between duration dependence (i.e., time spent in guardianship) and children's development (expressed as age). Overall, 17.3% of children reentered care by 2017. Early adolescents, age 13–15 years (HR = 1.63, p < .001), and late adolescents, age 16–17 years (HR = 1.93, p < .001), had an increased hazard of reentry compared with children under the age of six. Children with a history of mental health concerns had more than twice the hazard of reentering than children without such a history (HR = 2.18, p < .001). Our findings indicate that transition to adolescence was associated with increased risk of reentry into care, highlighting the need for guardianship support services leading up to, and during, this child developmental stage.